Modelling Hourly Vehicle Flows by a Finite Mixture of Simple Circular Normal Distributions - Kromer, Pavel; Hasal, Martin; Nowakova, Jana; Heckenbergerová, Jana; Musilek, Petr (IEEE (Institute of Electrical and Electronics Engineers), 2018)
Accurate modelling and representation of traffic flows is an important element of intelligent transportation systems, urban planning, and smart environments in general. In this work, location-specific hourly traffic flows are represented by finite mixtures of circular normal statistical distributions. The parameters of the finite mixtures are found by differential evolution, an evolutionary algorithm that is able to fit the statistical models to data with a high level of accuracy. The results are represented by circular plots that can be used as a form of visually appealing and easily understandable fingerprints of the underlying traffic flow patterns.
Modelování hodinového dopravního toku s použitím směsi jednoduchých kruhových normálních rozdělení
Keywords: traffic flow modelling; finite mixture of circular normal statistical distributions; differential evolution; polar plot; modelování dopravního toku; směs jednoduchých kruhových normálních rozdělení; diferencální evoluce; kruhový graf